Farmers’ perception of enablers and barriers to the adoption of renewable energy technologies for farming: a case study of the Lawra Municipality in the Upper West Region of Ghana - Ransford Teng-viel Karbo; Lynn J. Frewer; Francisco J. Areal; Albert Boaitey; Glyn Jones (Discover Agriculture)
Abstract Understanding farmers’ adoption behaviours towards new technological innovations is key to facilitating the widespread use of new sustainable farming practices. Renewable energy technologies, including solar and biomass, can provide substantial benefits to farmers when adopted and used to support farm-based activities. At present, the adoption of renewable energy technology for farming in Ghanaian agriculture is low and factors accounting for this development need to be understood if policy interventions are to be developed to mitigate this. This research aims to understand the barriers and enablers of renewable energy technology in Ghanaian agriculture as perceived by farmers and compared to other stakeholders. Purposive and snowballing non-probability sampling techniques were used. A semi-structured interview protocol was developed and used for in-depth interviews involving farmers (n = 36) in Lawra Municipality and stakeholders (n = 7) within the renewable energy ecosystem in Ghana. The data were analysed using NVivo analytical software and thematic analysis technique under the lens of the Decomposed Theory of Planned Behaviour. The results indicated that farmers perceived usefulness, ease of use, compatibility, peer and external influences, self-efficacy, technology, and resource-facilitating conditions to be enablers of renewable energy technology adoption. Initial high cost, gender imbalance in decision-making, and farmer misconceptions about adopting renewable energy technology were identified as barriers. Stakeholders’ roles in promoting renewable energy technology adoption for farming included policy development, financial support and logistical support provision, organising technology piloting and training of farmers, and institutional collaborations. There is a need to increase the capacity building of farmers through field demonstrations and technical support networks. The broader stakeholder community should co-develop a Research and Development (R&D) agenda that focuses on providing localised renewable energy technology solutions compatible with farmers’ needs and farming context.